Protein C and Protein S Levels in Î²-Thalassemia Major Patients in Erbil, Kurdistan Region - Hadi, Tareefa Kakakhan; Mohammad, Nawsherwan Sadiq; Nooruldin, Saran Abdulqadir (Cellular and Molecular Biology, 2020)
Oxygen is transported in the blood through red blood cells and a protein called hemoglobin. The protein consists of two alpha and two beta chains. The lack of any of these chains is caused by the malfunction of the genes that produce them, and can lead to a genetic disease called thalassemia. In Î²-thalassemia, hemoglobin does not produce enough beta protein. According to mild to severe effects on the body, Î²-thalassemia is divided into three types minor, interstitial and major thalassemia. There are increasing risks for thrombosis complications in thalassemia major. The purpose of this study was to evaluate protein C and protein S levels in Î²-thalassemia major and their association to the hypercoagulable state. Seventy patients with Î²–thalassemia major and 35 apparently healthy subjects as a control group were investigated for protein C and protein S. The mean of protein C (71.31%) and protein S (34.3%) levels were significantly reduced in Î²- thalassemia major patients in comparison with control subjects (p-value <0.001). Mean of fibrinogen level (2.42) g/l was significantly decreased in Î²-thalassemia major patients while the mean of D dimer level (0.43) Î¼g/ml was significantly increased in comparison to control subjects (p-value 0.001). This study demonstrates a chronic hypercoagulable state in B- thalassemia major patients.